Community Support Facilities - Vidallo, Rene R.; Bayot, Ruvicyn S.; Rosimo, Magnolia M.; Gonsalves, Julian Francis (2019)
The poster presents a brief description of farmer-managed community-based facilities established in climate-smart villages.